Post-Release Health Insurance Utilization Among Ex-Prisoners: A Scoping Review - Khaerunnisa, Icha; Andriany, Megah; Dwiantoro, Luky (Kesmas, 2025)
The lack of health insurance coverage after prison release significantly reduces access to essential healthcare services, hindering the continuity of care during community reintegration. The evidence on studies of health insurance use following prison release is limited. This scoping review aimed to summarize research on health insurance utilization after release from prison. Literature searches were conducted across databases including ScienceDirect, PubMed, and Scopus. Relevant articles were selected through a two-stage screening process. Data were extracted from the included studies and presented in tabular and descriptive formats. The keywords used were "health insurance AND post-release" and "inmates OR prisoners." This scoping review showed that post-release health insurance utilization varied internationally. Coverage gaps, such as those in the United States, limit access to and continuity of care, whereas Canada and Australia provide more stable services. Barriers included administrative challenges, housing and employment instability, stigma, and poor coordination within the health system. The findings highlight the influence of national insurance frameworks and the need for policies supporting prerelease-release enrollment, coverage continuity, cross-sector collaboration, and adherence to the World Health Organization and Nelson Mandela Rules for equitable healthcare.